2019
DOI: 10.1016/j.psychres.2019.01.077
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness stigma among Pacific Islanders

Abstract: Native Hawaiians and other Pacific Islanders (NHPI) rarely seek mental health treatment for reasons that are minimally understood. To assess the mental illness stigma context in NHPI communities that may be contributing to low help-seeking, this study collected novel stigma data from two large U.S. NHPI communities from October 2017-January 2018, then compared this data to national stigma data from the U.S. public. Survey data were collected from 222 communitydwelling NHPI participants recruited by research-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…Lastly, Samoan participants reported higher levels for nearly all positive and negative e-cigarette outcome expectancies vs. Marshallese participants, which may indicate greater awareness/exposure among Samoan young adults to e-cigarettes and/or e-cigarette marketing (Pokhrel et al, 2018a). Possible explanations for this pattern that could be explored in future research include potentially (1) greater access to, or penetration of, e-cigarettes in urban Los Angeles County NHPI vs. rural Arkansas NHPI communities; (2) greater susceptibility of Samoan young adults to ecigarette messaging/marketing (Mantey et al, 2016); or (3) greater US acculturation among Samoans vs. Marshallese, as shown in prior research (Subica et al, 2019b).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Lastly, Samoan participants reported higher levels for nearly all positive and negative e-cigarette outcome expectancies vs. Marshallese participants, which may indicate greater awareness/exposure among Samoan young adults to e-cigarettes and/or e-cigarette marketing (Pokhrel et al, 2018a). Possible explanations for this pattern that could be explored in future research include potentially (1) greater access to, or penetration of, e-cigarettes in urban Los Angeles County NHPI vs. rural Arkansas NHPI communities; (2) greater susceptibility of Samoan young adults to ecigarette messaging/marketing (Mantey et al, 2016); or (3) greater US acculturation among Samoans vs. Marshallese, as shown in prior research (Subica et al, 2019b).…”
Section: Discussionmentioning
confidence: 71%
“…The main exclusion criterion was lack of English reading and writing fluency (as determined by staff during the informed consent process). Participants were recruited using a non-probabilistic, respondent-driven sampling approach (Mays & Pope, 1995) used to capture representative community samples in earlier NHPI studies (Subica et al, 2019a(Subica et al, , 2019b. This involved NHPI staff recruiting participants directly from diverse community settings where NHPI young adults congregate (e.g.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…Like other people marked by historic trauma, Marshallese distrust health care providers and researchers ( 32 ). Public health research in other areas (eg, diabetes, prenatal care) among the Marshallese population documented barriers at individual, interpersonal, organizational, community, and policy levels ( 33 ) and showed that stigma may inhibit help-seeking behaviors ( 34 ).…”
mentioning
confidence: 99%
“…These data suggest that economic barriers might prevent adolescents in the CNMI from accessing and receiving proper mental health care, such as counseling and therapy. Further research is also necessary to investigate the fear and stigmatization surrounding mental health in the Pacific Islands, as these may have acted as social barriers to adolescents consulting mental health professionals [29].…”
Section: Discussionmentioning
confidence: 99%